1987
DOI: 10.1002/syn.890010104
|View full text |Cite
|
Sign up to set email alerts
|

Development of presynaptic specializations induced by basic polypeptide‐coated latex beads in spinal cord cultures

Abstract: The development of the neuromuscular synapse is initiated by an interaction between the motoneuron processes and the skeletal muscle. Previously we showed that basic polypeptide-coated latex beads can mimic the nerve in effecting a postsynaptic differentiation (Peng, H.B. and Cheng, P.-C.: J. Neurosci., 2:1760-1774, 1982). In this study, we examined whether these beads can also induce a presynaptic differentiation along the nerve processes. Explant cultures were prepared from the spinal cords of Xenopus larvae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
(39 reference statements)
0
20
0
Order By: Relevance
“…PDL-coated beads induce membrane adhesion followed by the subplasmalemmal clustering of synaptic vesicle complexes under the adhesion site within axons Previous studies (Burry, 1980(Burry, , 1982Peng et al, 1987) revealed that cultures of cerebellar granule cells were capable of forming contact-induced clusters of vesicles within 24 h on PLL-coated beads. To further investigate this phenomenon, low-density hippocampal cultures were grown (to DIV7, DIV15, or DIV21) and thereafter incubated with 7 m polystyrene beads coated with PDL (50 g/ml) (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…PDL-coated beads induce membrane adhesion followed by the subplasmalemmal clustering of synaptic vesicle complexes under the adhesion site within axons Previous studies (Burry, 1980(Burry, , 1982Peng et al, 1987) revealed that cultures of cerebellar granule cells were capable of forming contact-induced clusters of vesicles within 24 h on PLL-coated beads. To further investigate this phenomenon, low-density hippocampal cultures were grown (to DIV7, DIV15, or DIV21) and thereafter incubated with 7 m polystyrene beads coated with PDL (50 g/ml) (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled fluorescence ratios are also shown for each category. 1982, 1983, 1985Peng et al, 1987). Because substrates were necessarily polybasic for the clustering effect to occur, it was concluded that electrostatic-based adhesion between an axon and its target represents the first step that triggers synapse assembly (Burry, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations